Effect of 95% Ethanol Khat Extract and Cathinone on in vitro Human Recombinant Cytochrome P450 (CYP) 2C9, CYP2D6, and CYP3A4 Activity - Sharoen Lim, Yu Ming; Athira Rafhana, Azidin; Yee Tze, Ung; Mustafa, Al‑Shagga; Mohammed Abdullah, Alshawsh; Zahurin, Mohamed; Chin Eng, Ong; Yan, Pan (Springer Nature, 2018)
Background and Objective A significant number of people worldwide consume khat on daily basis. Long term of khat chewing has shown negative impact on several organ systems. It is likely that these people are co-administered khat preparations and conventional medication, which may lead to khat-drug interactions. This study aimed to reveal the inhibitory potencies of khat ethanol extract (KEE) and its major active ingredient (cathinone) on human cytochrome P450 (CYP) 2C9, CYP2D6, and CYP3A4 enzymes activities, which are collectively responsible for metabolizing 70–80% clinically used drugs.